New rules, same practice? Analysing UN development system reform effects at the country level - Silke Weinlich; Max-Otto Baumann; Maria Cassens-Sasse; Rebecca Hadank-Rauch; Franziska Leibbrandt; Marie Pardey; Manuel Simon; Anina Strey (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
With its unique multilateral assets, the United Nations Development System (UNDS) should be playing a key role in assisting governments and other stakeholders with their implementation of the 2030 Agenda for Sustainable Development. But this requires change. Despite improvements in recent decades, too often the UNDS has continued to act as a loose assemblage of competing entities, undermining its effective support for Sustainable Development Goal (SDG) implementation. It is against that backdrop that the UNDS has been undergoing an extensive reform - that was decided on in 2018 and has been implemented since 2019 - to provide more coherent, integrated support in line with requirements of the 2030 Agenda to United Nations (UN) programme countries. What effects have the reforms yielded at the country level? This paper presents the main findings, conclusions and recommendations from our research on UNDS reform implementation. It does so with a focus on reform-induced changes towards what we call a strengthened, collective offer at the country level. Overall, our research shows that reform implementation is moving the needle on the quality of the collective offer. In particular, with regard to its institutional element, we observed that the reform has fostered change in how UN country teams work together that is in line with what the 2030 Agenda demands. Institutional changes allow for increased cross-organisational and cross-sectoral coordination, which could potentially lead to increased policy coherence. [...]
Keywords: 330